CODESRIA Bulletin Online, No. 11, June 2021: Reading History from the Bottom Up - From Citizen and Subject to Neither Settler Nor Native - Ibrahim Abdullah (CODESRIA Bulletin, 2021)
Always bear in mind that the people are not fighting for ideas, for the things in anyone’s head. They are fighting to win material benefits, to live better and in peace, to see their lives go forward, to guarantee the future of their children.1 (Amilcar Cabral) From the publication of Citizen and Subject in 1996 as the premier tome in his celebrated trilogy, which dealt with citizenship in Africa, to the release of his recent book, Neither Settler Nor Native, which deals with citizenship as a troubling global unfinished business, Mahmood Mamdani has moved from jettisoning ‘How Europe Underdeveloped Africa’ as a research problematic to substituting ‘How Europe Ruled Africa’2 as the conceptual anchor in the burgeoning field of global citizenship studies. This methodological shift, and the consequent subverting of political economy in reframing the study of contemporary Africa and the legacy of late colonialism, constitutes the singular analytical thread linking Mamdani’s oeuvres on the citizenship question, not only in Africa but globally. Mamdani’s bold intervention in shifting the problematic from market-based oppression to governance-induced oppression and juridical violence from above raises complex and contradictory questions in how he frames and deploys his emancipatory discourse. From his original Africa-centred perspective, to a global comparative reach covering Germany and Israeli/Palestine, Mamdani finally offers a prescription that will be debated for years to come—embrace the South African option and let us all simply be survivors in the name of peace! In what follows below I offer a personal reading of Mamdani’s Neither Settler Nor Native, via his celebrated trilogy—Citizen and Subject, When Victims Become Killers and Saviors and Survivors—together with his prolegomena/interlude: From Citizen to Refugee and Define and Rule. This expansive longue durée pathway in making sense of Mamdani’s latest book takes us from Africa to EuroAmerica and Asia; from the local to the global; from nineteenthand twentieth-century African history to the global history of colonialism and oppression broadly defined and, of course, the genesis of the colonial world inaugurated via the fifteenth-century mercantile exploration and ‘discovery’ of the socalled New World. This revisionist political project from below, a truly counter-colonial script, has to be read as a radical reinterpretation of the global history of settlercolonial domination—Mamdani calls it colonial modernity —albeit through the prism of African historical realities. And it is significant that Mamdani selected 1492, not 1648, as his starting point for investigating the genesis of settlercolonial domination. The point of departure for understanding this trilogy is Mamdani’s autobiographical work, From Citizen to Refugee (1973). For it is here that Mamdani lays the groundwork for what was to become his original contribution to understanding contemporary Africa and the legacy of late colonialism. Mamdani skilfully weaves the historical, the sociological, the political and the economic in thinking through why Idi Amin did what he did after the January 1971 coup d’état in Uganda. His analysis of race and class, and his discussion of colonialism and the contradictions inherent in postcolonial Uganda, were conducted within the framework of Marxian political economy before his sojourn in Dar es Salaam. It is doubtful whether, at that point, Mamdani had elaborated any longterm research project that would have foreshadowed his singular contribution to citizenship studies—his now famous trilogy, for the young Mamdani was yet to turn in his doctoral dissertation. From Citizen to Refugee constitutes the foundational text for the clearly laid-out and well-argued trilogy that was rolled out eventually, two decades later. Here is a personal political experience, a crisp autobiographical intervention, weaponised in the service of liberation. The relevance of this text in shaping his subsequent contribution has been neglected by all in thinking through his magisterial intervention in the field of citizenship studies. Of his trilogy, Citizen and Subject is arguably the most read and engaged with of the volumes, and has been debated and critiqued far more than the other two—When Victims Become Killers and Saviors and Survivors. However, it is virtually impossible to meaningfully engage with Mamdani’s work on citizenship if one’s interest begins and ends with Citizen and Subject. The first course in his citizenship menu is both a methodological exposé and a theoretical critique of Africanists’ history and politics—those whom Mamdani disparagingly refers to as ‘many a stargazing academic perched in distant ivory towers’. Yet it deals more with subjecthood than with citizenship, his numerous critics charge. This criticism, I want to suggest, carries weight only if and when Citizen and Subject is read as a stand-alone text. But such a reading strategy takes away the full import of Mamdani’s contribution to citizenship studies globally. It is when Citizen and Subject is read as part of a trilogy that it comes alive as the analytical anchor/framework for the trilogy. It stands out as the normative and foundational base within which the structures that were to produce ethnicity/tribalism were framed and analysed. As Mamdani reminds us in When Victims Become Killers, ‘no one wrote of how Europe ruled Africa’. What was written and debated was how Europe underdeveloped Africa. Yet it is how Africa was (mis)ruled, Mamdani forcefully argues, that made it possible for resistance from below to reproduce the very structures it sought to transcend—a tribalised post-colony in which ethnicity was privileged as the norm. This, sadly, remains the enduring tragedy of postcolonial Africa. In the first volume Mamdani used examples from Uganda and South Africa to demonstrate how centralised/decentralised despotism produced a bifurcated state that henceforth became the proverbial birthmark of the postcolonial state. And this birthmark—ethnic through and through—together with race, gained empirical weight in the two subsequent volumes that deal with Rwanda and Sudan. When Victims Become Killers, the second volume in the trilogy, wrestles with the April 1994 genocide in Rwanda. Deploying the everchanging categories of natives/ indigenes/settlers, Mamdani takes us to what became the Rwandan state from its inception to the end of colonial rule. His emphasis is on the changing dynamics in state–society relations involving the two dominant groups: Tutsi and Hutu. And his objective is to explain the concrete conditions within which genocide became ‘thinkable’. The thinkability of genocide in a society peopled by two national groups who speak the same language and share the same culture has to be explained from the perspective of their longdrawn interaction—what Mamdani tirelessly refers to as ‘historicizing’ their relationship, warts and all. Describing the genocide as a native genocide—‘those who saw themselves as sons of the soil’ in a final push to do away with alien ‘presence’—he contends that ‘The analytical challenge is to understand the historical dynamic through which Hutu and Tutsi came to be synonyms for native and settler.’ Mamdani is no doubt uncomfortable with ethnicity when deployed as a primordial and instrumentalist category. For him, ethnicity has to be understood as a political identity. ‘By understanding political identities as embedded in particular institutions’, he tells us, ‘they become historical not primordial’ and ‘institutionally durable’, not amenable ‘for instant manipulation by those who seek power’. ‘To understand how tribe and race got animated as political identities’, he tells us ‘we need to look at how the law breathed life into them.’ Here is Mamdani at his best expounding on what is unarguably the central pillar of his conceptual anchor: ‘every state form generates specific political identities: direct rule tended to generate race based political identities: settler/native! Indirect rule … tended to mitigate the settler-native dialectic by fracturing the race consciousness of natives into multiple and separate ethnic consciousness’. If When Victims Become Killers is about two national groups with the same language and shared culture, Saviors and Survivors, the third tome in the trilogy, is about different groups who share the same religion and culture at the centre of which are race and the perennial making/remaking of space based on control and access to land. If there was genocide in one there was near-genocide in the other— a point that Mamdani laboured to hammer home against the backdrop of the militant right-wing intervention that had coalesced around the Save Darfur campaign, which erroneously claimed that Arabs were killing ‘black’ Africans in Darfur. Mamdani offers a materialist analysis of the conflict in Darfur, which began as a civil war in 1987–89 between nomadic pastoralists and peasants over fertile land in the south, triggered by a severe drought that had expanded the Sahara desert by more than ninety-five kilometres in forty years. He illustrates how the British colonialists had artificially tribalised Darfur, dividing its population into ‘natives’ and ‘settlers’, and created homelands for the former at the expense of the latter. How the war intensified in the 1990s, when the Sudanese government tried unsuccessfully to address the problem by creating homelands for ‘tribes’ without access to land, complicated an already complex situation. This context is key in understanding the drama around the war and its conflagration. The spillover of the war into Chad and the regionalisation of the conflict involving nations from different countries also brought Cold War warriors and the Israelis. Thus globalised, it became impossible to shift through the conflicting and competing interests— from Ghadaffi to Reagan et al. In the two major states he examines—the Funj Sultanate and Darfur—population looms large in the complexity of being an Arab (‘black’ and ‘white’) and of having access to land (dar/darless). This leads him to look at the pre-history of Funj and Darfur state before the Mahdist State was created. By restoring the Fur Kingdom after conquest, the British began a process of ‘retribalisation’. The indirect rule system imposed from above made place coterminous with ethnicity. Thus, Dar Zaghawa became an ‘ethnic territory in which a particular group had legal jurisdiction’. Desertification/environmental degradation and the move to the south for land and water complicated the situation. In the end the battle over land was ethnicised and racialised. Two conceptual observations are in order here. What seems to stand out in Mamdani’s trilogy is the ethnic/‘tribal’ in the making/ re-making of citizenship. First, the postcolonial state is ‘deracialised’—his words. In Sudan and South Africa he discusses race and ethnicity. Here, race and ‘tribe’ are the defining markers in all their complexities—from black Arab to cultural Arab to Afrikaner and Bantu ‘tribes’. We do not see oppressed minorities qua oppressed minorities—women and youth are left out of the script, missing as it were. Much more important is the total neglect of the Khoisan in South Africa and the Batwa in Rwanda—so-called aboriginals. Why neglect these aboriginals in Africa only to put them at the centre in explicating the genesis of the settler state in the United States? Second, if ethnicity/tribe are supposedly the warp and woof of citizenship in Africa, could that be read as Africa’s contribution to citizenship studies? Or, better still, the curse of the white man’s burden, as Basil Davidson’s once framed it? Put differently, why would a category that arguably atrophied elsewhere stubbornly refuse to go away in Africa? Or is this the case? Mamdani has not posed this question, the lingering refusal of ethnicity to go away, or attempted to provide an answer, he has explored only how the rural-urban divide and the ethnic question were (mis) handled in the post-colony by radical as well as conservative states. Yet his conclusions and prescriptions suggest that taming the ethnic beast is at the heart of the citizenship question in contemporary Africa. Is ethnicity/tribalism not laced with citizenship everywhere? And is tribalism not a universal category that rocks and undermines/ undergirds citizenship everywhere? Neither Settler Nor Native: The Making and Unmaking of Permanent Minorities builds on Mamdani’s trilogy by universalising and expanding the argument presented in it. It is a magisterial synthesis, and a bottom-up approach, looking at settler colonialism as a global system of domination. The five chapters are contoured by the argument that was originally rolled out in Citizen and Subject. Three chapters deal with areas in which Mamdani originally had no research interest (Germany, the US and Israeli/Palestine history)3 and two deal with the African situation, in South Africa and South Sudan, areas where he had done original research. The chapter on South Sudan, unlike Saviors and Survivors, the last volume in the trilogy, deals with Africa’s newest nation-state. The most important intervention in this new book—apart from its expansive global swing—is the introduction of two new formulations: the political community as a vehicle in the process of societal transformation, and the notion of political decolonisation. Both formulations are, however, linked. They are both a critique of the standard prescriptions proffered under neoliberal guidance and tutelage, but they can also be read as an autocritique of Mamdani’s earlier formulation presented in his famed trilogy. The making and unmaking of permanent minorities is a re-interpretation of US and Israeli/Palestinian history through the prism of the African experience. The hegemonic white power superstructure and the subordination of the indigenous peoples via the native-settler dialectic demonstrate the universality of the native-settler binary, which arguably defines all colonial socioeconomic formations. The US example became the template for others to emulate/appropriate—the Third Reich in Germany and Zionism in the Israeli settler state. The reproduction of this oppressive and dehumanising governance framework at the global level seems to suggest this pathway is the dominant route to settler colonialism. But is this really the case? With reference to the US and Israeli examples, Mamdani argues for a transformation outside the Nuremburg/ human rights paradigm, which has been heralded by neoliberal ideologues as the true way to salvation. Here he uses the South African example as the harbinger of hope—a ‘deracialised’ society in which the state is seemingly decoupled from the nation. The conjoined nationstate reality, Mamdani insists, remains the source of the problem because it conduces and even reproduces primordialism. Yet Mamdani’s prescriptive pathway, seemingly anchored on privileging the South African experience in crafting a meaningful ‘adversarial’ politics, skirts an old leftist debate that was inspired by the Fanonist problematic, the notion of true and false decolonisation yanked from the quintessential biblical spirit—of the first shall be the last. This formulation, which privileges armed struggle against constitutional negotiation, found expression in the so-called socialist pathway to development versus the capitalist pathway, which held sway in the first two decades of independence. Yet, as it later transpired, neither socialist nor capitalist could deliver the proverbial dividend of democracy. The popular masses, the peasantry and the labouring population, Africa’s teeming urban poor and her beleaguered working classes (to use a tired leftist framing), did not experience what Nkrumah had envisaged when he exhorted them to ‘seek ye first the political kingdom’. Besides that, all the subaltern categories deployed in Mamdani’s two and half decades of labour—from his trilogy to Neither Settler Nor Native—in defining the burgeoning field of African/global citizenship studies—(citizen/subject/saviours/ survivors/ victims/killers/settler/native)—appear continually in flux, a result of their constantly being made and remade (work in progress?). By privileging how Africa was ruled/ is ruled in crafting tools for our collective emancipation, Mamdani seemingly ends up focusing more on structure than historical agency. This structuration from above at the expense of agency from below has no doubt enriched our understanding of how subalterns were conditioned from above but not of their intervention/role as conscious historical actors of their own making. Historically, how subalterns handle their individual/collective making from above and without and how they deploy that experience in shaping their lives should be a central part of the narrative of their collective emancipation. This seemingly one-sided narrative in Neither Settler Nor Native comes out clearly in the South African and South Sudanese experience. Put differently, what would ‘decolonising the political’ mean for the popular masses in contemporary South Africa and South Sudan? And how would a ‘new autobiography’ change their livelihood/ objective economic conditions? Lastly, who would write that ‘new autobiography’ and from what perspective or standpoint? Mamdani’s notion that we could all be ‘survivors’ in the face of serious/complex issues around race and ethnicity does not speak to the above questions nor does it identify the forces that would constitute the emancipatory vehicle that would advance the collective interests of the undifferentiated survivors—a notion that seemingly evokes memories of unity in the name of the nationstate—a category that Mamdani himself militantly disowns in Neither Settler Nor Native. On these important questions Neither Settler Nor Native is painfully silent. Mamdani, the self-described ‘incorrigible optimist’, has crafted a continental and global pathway to an imagined political community sans class struggle, together with a political community where race and ethnicity would be held in abeyance by survivors in a post nation-state. How this seemingly one-size-fits-all prescription pans out in the desperate case studies presented in his monumental synthesis remains to be seen. Notes Amilcar Cabral, 1965, Tell No Lies, Claim No Easy Victories, in Handyside, R., ed., 1970, Revolution in Guinea: Selected Texts by Amilcar Cabral, New York: Monthly Review Press. This formulation of the author’s conceptual and methodological shift from political economy to the institutional/juridical basis of colonial domination/oppression was originally presented in When Victims Become Killers. But it appears also in outline form in Citizen and Subject and in its fully developed form in his latest book, Neither Settler Nor Native. Mamdani’s published articles on political identities and Nuremburg do not deal with the Palestine/ Israeli question. And his Good Muslim Bad Muslim, the closest he has come to discussing US politics and history, does not deal with the issues of citizenship and exclusivity in US history.